The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s13014-015-0468-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative dosimetric findings using accelerated partial breast irradiation across five catheter subtypes

Abstract: PurposeAccelerated partial breast irradiation (APBI) with balloon and strut adjusted volume implants (SAVI) show promising results with excellent tumor control and minimal toxicity. Knowing the factors that contribute to a high skin dose, rib dose, and D95 coverage may reduce toxicity, improve tumor control, and help properly predict patient outcomes following APBI.Methods and materialsA retrospective analysis of 594 patients treated with brachytherapy based APBI at a single institution from May 2008 to Septem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…From these data, a D max of 120-125% of the PD has been proposed, 4,5 wherein the preferred D max should be as low as 100%. 6,7 Thus, although it was unsurprising that ribs 4 and 5 were fractured in this case report, the finding of rib 6 was unexpected. The patient had no known risk factors, such as primary or secondary osteoporosis.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…From these data, a D max of 120-125% of the PD has been proposed, 4,5 wherein the preferred D max should be as low as 100%. 6,7 Thus, although it was unsurprising that ribs 4 and 5 were fractured in this case report, the finding of rib 6 was unexpected. The patient had no known risk factors, such as primary or secondary osteoporosis.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, most studies have reported rib D max as a chest wall/rib parameter, with some measuring the balloon‐to‐rib distance as well. From these data, a D max of 120–125% of the PD has been proposed, 4,5 wherein the preferred D max should be as low as 100% 6,7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accelerated partial-breast irradiation using balloon highdose-rate (HDR) brachytherapy has provided excellent outcomes, comparable tumor control, and low toxicity rates when compared to whole-breast irradiation [1][2][3][4][5]. One of the important outcomes following balloon breast HDR brachytherapy is skin toxicity, and the maximum skin dose is a key dosimetric parameter in balloon HDR breast brachytherapy treatment planning [2,[6][7][8][9]. Hence, the skin maximum point dose was limited to ≤ 145% of the prescribed dose in the use of a single-lumen MammoSite® balloon applicator (Hologic Inc., Bedford, MA, USA) [10].…”
Section: Introductionmentioning
confidence: 99%